Time Domain Reflectometry Concept for Underground Cable Fault Detection using CST Simulation Software - Zainal, Adilla Fariha; Othman, Nordiana Azlin (Evolution in Electrical and Electronic Engineering, 2023)
In order to help reduce the ratio of fatal accidents involving cable maintenance and highway users, the implementation of the time domain concept for underground cable fault detection using Computer Simulation Technology (CST) Cable Studio software was used. This system was designed to improve the detection of faults in underground cables by focusing the time domain reflectometry (TDR) signal reflect in normal and fault conditions. This approach is one of the safety procedures used by workers and highway users to avoid accidents and damage. There are several adjustments that need to be made in order to make the problem described appropriate for the working environment and to obtain a better underground fault detector. To obtain the analysis findings of the strength and integrity design, this project was evaluated using CST cable simulation. The properties of cable in normal and fault conditions for street lighting must be focused on to achieve and analyse the results obtained in order to complete this project. The result obtained for each condition ideal, short, open, and short and open circuit will be analysed to see the difference of Time Domain signals that will produce.